PENGARUH STRES KERJA, KECERDASAN EMOSIONAL, KECERDASAN INTELEKTUAL DAN DUKUNGAN ORGANISASI TERHADAP KINERJA PEGAWAI DILINGKUNGAN BADAN PENGELOLA KEUANGAN DAN ASET DAERAH KABUPATEN LABUHANBATU - Novrihan Leily Nasution (LPPM Universitas Labuhanbatu, 2020)
The purpose of this study was to determine the influence of job stress, emotional intelligence, intelligence intektual and organizational support on employee performance in LingkunganBadan Finance and Asset Management Daerah Kabupaten Labuhanbatu either partially or simultaneously.Data Collection techniques in this study using interviews, questionnaires and literature study. Workmanship methods of data analysis using the software SPSS 26.0 for Windows. This study uses a sample of 30 employees is taken using a census techniques.The results of the research based on the test simultaneously (F test) showed that simultaneous (concurrent) job stress, emotional intelligence, intellectual intelligence and support of the organization simultaneously have a significant effect on the performance of employees in the Finance and Asset Management Agency Daerah Kabupaten Labuhanbatu, where the value of Fcount (5,866) > Ftable (2,759) with a significance 0,002 < 0,05. The results of testing the hypothesis partially (t test) showed that job stress (X1) has positive and significant effect on employee performance in Finance and Asset Management Agency Daerah Kabupaten Labuhanbatu, where t (2,500) > ttable (1,25) with a significance 0,019 < 0,05. emotional intelligence(X2) has positive and significant effect on employee performance in Finance and Asset Management Agency Daerah Kabupaten Labuhanbatu, where the value of (2,076) > ttable (1,25) with a significance 0.048% ownership of < 0.05, intellectual intelligence (X3) has a positive effect but not significant to the performance of employees in the Finance and Asset Management Agency Daerah Kabupaten Labuhanbatu, where the value of tcount (0,402) < ttable (1,25) with a significance 0,691> 0,05. Based on the test results of determination shows that of 48.8% variable employee performance can be explained by job stress, emotional intelligence, intellectual intelligence and organizational support. While the rest of 51.2% can be explained by other factors not examined in this study.